Vehicular Channel in Urban Environments at 23 GHz for Flexible Access Common Spectrum Application - Longhe Wang; Bo Ai; Jingya Yang; Hao Qiu; Wanqiao Wang; Ke Guan (International Journal of Antennas and Propagation)
With the development of the vehicular network, new radio technologies have been in the spotlight for maximizing the utilization of the limited radio spectrum resource while accommodating the increasing amount of services and applications in the wireless mobile networks. New spectrum policies based on dynamic spectrum access technology such as flexible access common spectrum (FACS) have been adopted by the Korea Communications Commission (KCC). 23 GHz bands have been allocated to FACS bands by the KCC, which is expected extensively for vehicular communications. The comprehensive knowledge on the radio channel is essential to effectively support the design, simulation, and development of such radio technologies. In this paper, the characteristics of 23 GHz vehicle-to-infrastructure (V2I) channels are simulated and extracted for the urban environment in Seoul. The path loss, shadow factor, Ricean K-factor, root-mean-square (RMS) delay spread, and angular spreads are characterized from the calibrated ray-tracing simulation results, and it can help researchers have a better understanding of the propagation channel for designing vehicular radio technologies and a communication system in a similar environment.